Developing a pedagogical problem solving view for mathematics teachers with two reflection programs - Bracha KRAMARSKI (International Electronic Journal of Elementary Education, 2009)
The study investigated the effects of two reflection support programs on elementary school mathematics teachers’ pedagogical problem solving view. Sixty-two teachers participated in a professional development program. Thirty teachers were assigned to the self-questioning (S_Q) training and thirty two teachers were assigned to the reflection discourse (R_D) training. The S_Q program was based on the IMPROVE self-questioning approach which emphasizes systematic discussion along the phases of mathematical or pedagogical problem solving as student and teacher. The R_D program emphasized discussion of standard based teaching and learning principles. Findings indicated that systematic reflection support (S_Q) is effective for developing mathematics PCK, and strengthening metacognitive knowledge of mathematics teachers, more than reflection discourse (R_D). No differences were found between the groups in developing beliefs about teaching mathematics in using problem solving view.